Philippines 2000 a vision for the nation. (Studio 5 Designs, Inc., 1996)
"Philippines 2000: A Vision for the Nation is a book of information, encouragement and inspiration. Originally conceived to be an interpretation of the vision of President Fidel V. Ramos, the book has, however, become more than a mere presentation of a Philippine President's vision and plans for his country."--Book jacket.